(untitled) (Communications in Computational Chemistry, 2025)
In the framework of a dynamic vibronic model, we report the influence of both local and nonlocal vibronic coupling on the vibronic energy levels for organic mixed-valence systems, and then evaluate their contributions to photoelectron spectroscopy of a realistic molecule as an example. Our results demonstrate that the variation of nonlocal vibronic coupling constant in the dimeric model doesn’t influence the relative positions of vibronic energy levels. For the spectrum simulated, it tries to maintain the constant difference 2t^0_ab between the splitting energy levels corresponding to two peaks of the first ionizations.